2014
DOI: 10.1186/s12879-014-0682-1
|View full text |Cite
|
Sign up to set email alerts
|

First report of Rickettsia felisin China

Abstract: BackgroundRickettsia felis is a recently described flea-borne spotted fever group Rickettsia that is an emerging human pathogen. Although there is information on the organism from around the world, there is no information on the organism in China.MethodsWe used a commercial ELISA to detect antibodies reactive against R. felis in blood samples and developed a PCR to detect the gltA of the organism in blood samples and external parasites.ResultsWe found reactive antibodies in people (16%; 28/180), dogs (47%; 128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
67
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 18 publications
5
67
1
1
Order By: Relevance
“…Since the first reports that rickettsiae could be propagated in mosquito cell lines, 9, 10 there has been growing evidence that mosquitoes can be infected with the organisms. 1, 2, 3, 4, 5 Our study provides further information on Rickettsia species in mosquitoes, in particular the common house mosquito Cx. pipiens that occurs widely in temperate areas of the world and feeds most commonly on a wide variety of bird species but also occasionally on people and a wide range of mammals.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…Since the first reports that rickettsiae could be propagated in mosquito cell lines, 9, 10 there has been growing evidence that mosquitoes can be infected with the organisms. 1, 2, 3, 4, 5 Our study provides further information on Rickettsia species in mosquitoes, in particular the common house mosquito Cx. pipiens that occurs widely in temperate areas of the world and feeds most commonly on a wide variety of bird species but also occasionally on people and a wide range of mammals.…”
mentioning
confidence: 78%
“…and Mansonia uniformis in Africa, 1, 2, 3 and Anopheles sinensis and Culex pipiens in China. 4 Further, it has been shown that Anopheles gambiae can be infected with R. felis and transmit the organism during feeding, indicating it might be a potential vector. 5 Finally, a new Rickettsia species has been found in An.…”
mentioning
confidence: 99%
See 3 more Smart Citations